Methodology for Evaluating the Cutting Force of Planar Technical Blades Used in Flatfish Processing - Zieliński, Bartosz; Chaciński, Tomasz; Pimenov, Danil Yurievich; Nadolny, Krzysztof (Micromachines (Basel), 2021)
In the food industry, there are many varieties of technical blades with different contours as well as different cutting edge geometries. The evaluation of the ability of technical blades to separate (cut) animal tissues is not a simple task and is usually based on the evaluation of the cutting effects in a technological process. This paper presents a methodology for evaluating the cutting force of technical blades used in food processing. A specially made test stand with numerical control was used in the study. Its application enabled a comparison of cutting force values for four different cutting edge geometries of planar knives used in the skinning operation of flat fishes. A unique feature of the conducted research was the use of a relatively high cutting speed value of vf = 214 mm/s, which corresponded to the real conditions of this process carried out in the industry. Obtained test results allow unambiguously choosing the most advantageous variant of knife geometry from among four different variants used for the tests. The results showed a clear relationship between the cutting force value and the value of the tip angle of the blades tested: for blades with the lowest tip angle, the lowest cutting force values were obtained.